Successful medical management of multiple 'Rattle' magnet ingestion in a dog. Issue 1 (1st March 2019) - Valiente, Paula; Florey, Jess
Abstract : Multiple magnet ingestion requires emergency treatment given the serious associated complications. A four‐year, 10‐month‐old male neutered Border collie was referred for investigation of generalised tonic‐clonic seizures. On presentation, there was an episode of vomiting and possible ingestion of two 'Rattle magnets'. Physical and neurological examination was unremarkable apart from mild cranial abdominal discomfort. Abdominal radiographs revealed the presence of two metallic foreign bodies suspected to be within the pyloric antrum and three mineralised foreign bodies within the small intestine. Endoscopy revealed the presence of one magnet in the pyloric antrum. After removal, a deep erosion of the gastric mucosa was observed. Gastroprotectants were administered and repeated abdominal radiographs showed the second magnet within the intestine. Thirty‐six hours later, the patient passed faeces containing three stones and one magnet and was discharged without further gastrointestinal signs or complications, prior to returning for neurological investigations.